Susceptibility of adult and larval stages of the horn fly, Haematobia irritans, to the entomopathogenic fungus Metarhizium anisopliae under field conditions - Mochi, Dinalva Alves [UNESP]; Monteiro, Antonio Carlos [UNESP]; Simi, Lucas Detogni [UNESP]; Sampaio, Alexandre Amstalden Moraes [UNESP] (Elsevier B.V., 2009)
The efficacy of M. anisopliae strain E9 as a biological insecticide for the adult and larval stages of H. irritans was assessed under field conditions. To assess larvicidal activity, nine heifers were randomly divided into three groups, which were maintained separated from each other. The first group ingested fungal spores encapsulated in alginate pellets. The second group ingested in natura spores that were grown on sterilized rice. In both groups, each animal received three meals a day, with each meal containing 2 x 10(10) conidia. The third group received no treatment and was used as a control. Fecal samples from manure and whole dung pats were collected from each of the three separate pastures on the day that the animals were allocated and on days 1, 3,6,9 and 12 afterwards. The fecal samples were tested for the presence of fungal colony forming units (CFU), and the emergence of horn flies was observed in the dung pats. Significantly less (P < 0.01) adult horn flies were found in dung pats of the group treated with encapsulated fungi (11.7) than in those from the heifers treated with conidia in natura (27.9) or from the control group (29.5). The fecal samples of the treated animals presented significantly higher numbers of M. anisopliae CFUs then those from the untreated controls. We found that on day 9 fecal samples from animals given microencapsulated conidia had significantly higher CFUs than those from animals treated with conidia in natura. To assess adulticide activity, four heifers were sprayed with a suspension of 3 x 10(10) aconidia l(-1) of M. anisopliae, and four control animals were sprayed with the same solution without conidial content. Four sprayings were done at five-day intervals, and all animals were photographed daily to observe the quantity of flies present. After the second spraying, we observed an average of 22.9 flies per animal; untreated heifers had an average of 43 flies per animal; thus, the treatment significantly (P < 0.05) decreases fly infestation. The results obtained from both tests show that M. anisopliae strain E9 has a pathogenic effect on H. irritans larvae in bovine manure when administered orally and on adult fly infestations when applied as a spray on the hosts. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Horn fly; Ectoparasite; Biological control; Pellets; Sodium alginate; Encapsulation